Trends in surgery and anesthesia practices during the COVID-19 pandemic: a nationwide analysis from South Korea’s Health Insurance Database - Ahn, EunJin; Kim, Hyo Jin; Bang, Si Ra (Frontiers in Medicine, 2025)
IntroductionThe coronavirus disease 2019 (COVID-19) pandemic has led to significant changes to global healthcare systems, particularly affecting surgical and anesthetic practices. This study investigated nationwide trend in anesthesia and surgery before and during the pandemic.MethodsThis retrospective, population-based study analyzed confirmed COVID-19 cases in the Korean National Health Information Database from 2019 to 2021. Anesthesia procedures were categorized into general anesthesia, regional anesthesia, and monitored anesthesia care (MAC). COVID-19 positive patients were defined as those with a confirmed diagnosis within 30 days before and after surgery. We analyzed anesthesia modality, patient characteristics, hospital type and COVID-19 trends.ResultsA total of 6,878,556 anesthesia procedures were recorded. The number of procedures decreased slightly in 2020 but increased in 2021. General anesthesia accounted for the majority of procedures. Regional anesthesia, especially brachial plexus block (BPB), and MAC showed an increasing trend. There was a positive correlation between monthly COVID-19 case counts and surgical volume. Most COVID-19 positive patients underwent surgery in general hospitals and received general anesthesia.ConclusionDespite the pandemic, overall surgical volume in South Korea remained relatively stable compared to global trends. The shift toward regional techniques like BPB suggests adaptation to reduce aerosol-generating procedures. These findings highlight the need for strategic allocation of resources and preparedness planning in future pandemics.